Japanese philosophers on society and culture Nishida Kitarō, Watsuji Tetsurō, and Kuki Shūzō - Mayeda, Graham (Lexington Books, 2020)
"What is culture? What can we learn from art, architecture, and fashion about how people relate? Can cultures embody ethical and moral ideals? These are just some of the questions addressed in this book on the cultural philosophy of three preeminent Japanese philosophers of the early twentieth century, Nishida Kitarō, Watsuji Tetsurō and Kuki Shūzō"--